Turbulent dispersion and evaporation of charged nanofuel droplet clouds under the influence of electrostatic fields - Weiand, Erik; Giusti, Andrea (International journal of spray and combustion dynamics, 2024)
The concept of smart combustion, where nanofuels and electromagnetic interactions are combined to enhance the flame characteristics and improve the control of the combustion process, is introduced as a new paradigm for next-generation hybrid propulsion systems. To gain further insight into the possibility of controlling the fuel location in a turbulent flow, the fundamental case of dispersion of a cloud of charged nanofuel droplets in initially homogeneous and isotropic turbulence under the action of electrostatic fields is investigated. Keeping electrical repulsion forces relatively small compared to the other forces, cases with and without evaporation are studied using direct numerical simulations for different strengths of the external electrostatic field. Results of the non-evaporating cases show that the use of external electrostatic fields enables the control of the location and velocity of the centre of mass of the cloud, with limited effect on the cloud dispersion, which is mainly determined by the background turbulence. Results for evaporating droplets in decaying turbulence show that external electrostatic forces enable a quick separation between cloud and vapour distribution in the case of fast-evaporating droplets. This separation could be further enhanced by designing nanomaterials with specific diffusion properties. This work is the first step towards developing smart combustion and provides new insight into the control of charged nanofuel droplet dynamics under the action of external electrostatic fields.